Impact of Psychosocial Factors on Patients’ Adjustment: A Pilot Study about Recurrence of Cancer - Yenkamala Mina Ananda (Challenges in Disease and Health Research Vol. 9, 2021)
Background: The need to prevent cancer lead us to propose three innovative courses of cancer as categories of disease. Aim: The goals of our research are to investigate the impact of various factors on cancer recurrence adaptation and to assess the quality of life, anxiety as a state, depression as a state, and disease evolution over a three-month period. Methods and Materials: We met 32 subjects after announcing the recurrence of their cancer during this longitudinal and prospective study, and we saw 21 of them again three months later. In two times of the study, we made fill out several questionnaires concerning various variables. Results: Our main findings suggest that the majority of the participants did not have a new cancer recurrence and that the implementation of a fighting strategy is representative of them. Our linear regressions and average comparisons enabled us several relations about to different categories of disease. Conclusion: Supportive therapies and stress management programmes would be beneficial for cancer patients who have had a recurrence.